SERUM 25 (OH) VITAMIN D AND ITS ROLE IN SECONDARY HYPERPARATHYROIDISM IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Yogi, Jaiprakash; Fiza, Bushra; Godara, Suraj; Sinha, Maheep (International Journal of Clinical and Biomedical Research, 2017)
Background & Objective: Chronic Kidney Disease (CKD) is emerging as an important public health problem across the world. In severe cases, the disease progresses towards end stage renal disease (ESRD) which is associated with several complications. In recent years, 25 (OH) Vitamin D has been identified as a risk factor for ESRD. Vitamin D plays a vital role in regulating parathyroid hormone (PTH) synthesis and release. Decreased Vitamin D levels are identified as a risk factor for secondary hyperparathyroidism (SHPT) which is one of the major complications of CKD and is associated with renal osteodystrophy. The present study was planned to assess the status of 25 (OH) Vitamin D and its role in secondary hyperparathyroidism in patients with CKD. Materials and Methods: The study was conducted on 50 diagnosed cases of CKD (stage 4 and 5), age < 60 years. Age and sex matched healthy subjects (n = 50) constituted the control group. Serum 25(OH) Vitamin D and iPTH were estimated for all the enrolled subjects. BMI and eGFR were also calculated. All variables were compared among the control and diseased group. Results: Vitamin D levels were significantly low in the CKD group as compared to the control group (p<0.001). 72% of the total CKD patients were deficient in Vitamin D levels. Serum iPTH was significantly higher in the CKD patients (p = 0.000). A significant negative correlation was observed between iPTH and Vitamin D (r = -0.614). Conclusion: The study suggests that patients of CKD are at high risk of Vitamin D deficiency. Vitamin D deficiency has a strong association with the pathogenesis of SHPT. KEYWORDS: Chronic Kidney Disease; Vitamin D; Parathyroid hormone; Secondary Hyperparathyroidism; End Stage Renal Disease.